2007
DOI: 10.1088/0953-2048/20/10/027
|View full text |Cite
|
Sign up to set email alerts
|

Composite metallic sheathes: the key to low-cost, high strength (Bi,Pb)2Sr2Ca2Cu3O10-based tapes?

Abstract: (Bi,Pb)2Sr2Ca2Cu3O10-based superconducting tapes were prepared by the powder-in-tube process, using a bimetallic sheath consisting of Ag and Ni. Ag was in contact with the superconducting ceramic core and acted as a protective layer against reaction between the external Ni sheath and the core. (Bi,Pb)2Sr2Ca2Cu3O10 phase formation was possible if a path for oxygen diffusion was opened in the Ni sheath. This was achieved by removing Ni on one edge of the tape edges by polishing. Transport critical current densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The white and black regions are the Ag layer and the ceramic core, respectively, 3 μm, respectively. However, due to the finite diffusing depth of Ni toward Ag during sintering periods [15,17], the thickness of Ag layer can be much thinner in industrial production. Meanwhile, Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The white and black regions are the Ag layer and the ceramic core, respectively, 3 μm, respectively. However, due to the finite diffusing depth of Ni toward Ag during sintering periods [15,17], the thickness of Ag layer can be much thinner in industrial production. Meanwhile, Figs.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is reported that in composite Ag-Ni ribbons, which are used as substrates for Bi-2212 tapes, Ag can prevent the diffusion of Ni toward the Bi-2212 layer [15,16]. Thereafter, Ag-Ni composite-sheathed Bi-2223 tapes using Ni as the outer sheath were successfully manufactured by Grivel et al [17] and Li et al [18]. Though this tape is promising for enhancing mechanical properties and reducing production costs, tapes with long length and multi-filament core have not yet been successfully fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…As the silver and silver alloys can meet these requirements, silver is mainly used as the inner tube material and silver alloy is used as outer tube structure during the preparation of Bi-2223/Ag tapes. Grive l [10] replaced the outer sheath material by nickel and improved the mechanical stability and current performance of composite. Liang [11] investigated that the superconducting tapes using silver alloy as the outer tube and inner tube had the better mechanical strength compared to the commercial tapes.…”
Section: Influence Of the Materials Properties On The Interface Deformmentioning
confidence: 99%
“…Bi 1.8 Pb 0.33 Sr 1.87 Ca 2.0 Cu 3.0 O 10 + δ (Bi‐2223) material is a typical ceramic material. Ag/Ni composite‐sheathed Bi‐2223 (Bi‐2223/Ag/Ni) superconducting tapes have been fabricated successfully by Grivel and Chen et al in recent years. Owing to the advanced Ag/Ni composite‐sheathed technique, Bi‐2223/Ag/Ni tapes that have lower cost and higher strength show great superiority relative to traditional Bi‐2223/Ag tapes.…”
Section: Introductionmentioning
confidence: 99%